MENCERMATI DAMPAK DIGITALISASI BAGI UMKM PASCA PANDEMI COVID 19 - Muhammad Vhikry; Ana Susi Mulyani (Sekolah Tinggi Pariwisata Mataram, 2023)
The COVID-19 pandemic has brought many difficulties and uncertainties to the social and trade world. MSMEs (Micro, Small and Medium Enterprises) are considered vulnerable and are therefore required to respond, change, and adapt their business models to survive while improving their performance. The crisis has forced business entities even such as MSMEs to move strategically towards the use of digital tech nology and the ability to utilize Information Technology (IT) into business operations. Digital marketing in the modern era like this is a very easy thing to find, therefore this must be a new benchmark for us as young teenagers in order to be at the forefront and compete to show our abilities in global business competition by providing the best in all field.In the era of digitalization like today we are required to be people who are creative in the face of increasingly fierce global competition, This digital technology was born out of the confines of space and time of consumers to distributors as well as producers to distributors. Therefore, the purpose of this study is to assess the relationship between the ability to utilize Digital Transformation, Innovation and the performance of business entities. This study used an interview survey. The findings show that Digital Transformation Capabilities have a positive relationship with Company Performance.